PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN GENERASI Z DI UD. LOTUSSAN STATIONARI SEMARANG - Kolin, Yohanes Don Bosko Sogan; Hendrawan Maranata, Bonaventura (Penerbit Lafadz Jaya, 2025)
This research explicitly tests the effect of work compensation and work discipline on the performance of generation Z employees at UD. Lotussan Stationari Semarang. This research is quantitative in nature, where data is obtained by distributing questionnaires to UD employees. Lotussan Stationari, especially those categorized as generation Z with a sample size of 100 employees using the purposive sampling method. The data analysis technique used is multiple linear regression analysis with a statistical program. Based on the research, it can be found that there is an effect of compensation and work discipline on the performance of generation Z employees at UD. Lotussan Stationari Semarang. In addition, based on the results of the simultaneous test, it was found that compensation and work discipline have a positive and significant effect on the performance of generation Z employees at UD. Lotussan Stationari Semarang.